Legal Awareness and National Resilience in The Socio-Cultural Field - Utama, Anang Puji (Universitas Negeri Malang, 2023)
The role of law as a regulator that can be a means of community control is a strategic tool in building national resilience. However, the law also requires obedience from the community as a departure from legal awareness. The norms in the law will only be norms without obedience from the community. This research is conducted using normative legal research methods, namely research by analyzing laws and regulations that apply or are applied to a particular legal problem. This paper aims to examine the relationship between law and national resilience in the socio-cultural field and examine efforts to improve national resilience through building public legal awareness in order to achieve a high level of legal obedience. The method is done through a literature study. The findings of this paper are the link between national resilience with awareness and obedience to the law needed for the smooth implementation of national development. The rule of law, as the nature of other rules, requires public obedience to obey or behave in accordance with the values in the law. This obedience requires legal awareness from the community. Legal awareness, public obedience, and national resilience in social aspects have a relationship with each other. High legal awareness will enable one to realize the level of obedience to the law that will strengthen national resilience.Kesadaran Hukum dan Ketahanan Nasional Bidang Sosial BudayaPeran hukum sebagai pengatur yang dapat menjadi alat kontrol masyarakat menjadi sarana strategis dalam membangun ketahanan nasional. Namun hukum juga menutut adanya ketaatan dari masyarakat sebagai berangkat dari kesadaran hukum. Norma yang ada di dalam hukum hanya akan menjadi norma semata tanpa adanya ketaatan dari masyarakat. Penelitian ini dilaksanakan dengan metode hukum normatif (normative legal research) yaitu penelitian dengan cara menganalisis peraturan perundang-undangan yang berlaku atau diterapkan pada suatu permasalahan hukum tertentu. Tulisan ini bertujuan untuk mengkaji keterkaitan hukum dengan ketahanan nasional bidang sosial budaya serta mengkaji upaya meningkatkan ketahahan nasional melalui membangun kesadaran hukum masyarakat guna mencapai tingkat ketaatan hukum yang tinggi. Metode yang dilakukan melalui studi literatur. Temuan dari tulisan ini adalah keterkaitan antara ketahanan nasional dengan kesadaran dan ketaatan pada hukum yang diperlukan bagi kelancaran pelaksanaan pembangunan nasional. Kaidah hukum sebagaimana sifat dari kaidah lainnya menuntut ketaatan masyarakat untuk mematuhi atau berperilaku sesuai dengan nilai-nilai yang ada di dalam hukum. Ketaatan ini menuntut adanya kesadaran hukum dari masyarakat. Kesadaran hukum, ketaatan masyarakat dan ketahanan nasional dalam aspek sosial mempunyai hubungan satu sama lain. Kesadaran hukum yang tinggi akan dapat mewujudkan tingkat ketaatan terhadap hukum yang akan memperkuat ketahanan nasional.